Haplotype diversity of 17 Y-chromosome STR loci in Han population from different areas of Sichuan Province, Southwest China. (May 2017) - Fan, Guangyao; Li, Wei; Ye, Yi; Li, Xuebo; Ge, Wendong; Yang, Yongqiang; Long, Bing
Highlights: The distribution of 17 Y-STR loci were analyzed in Sichuan, China. The observed haplotype diversity and discrimination capacity were calculated. Pairwise Rst values were evaluated in AMOVA analysis and visualized through MDS. The Sichuan Han exhibited no significant genetic difference to both Mongolian and Manchu. Abstract: The distribution of 17 Y-chromosome short tandem repeat (STR) loci, included in the AmpF l STR®Yfiler™ amplification kit, were analyzed in six different samplings (N = 878) from Sichuan, China. Haplotype diversity and discrimination capacity (DC) values were calculated. Pairwise Rst values were evaluated in AMOVA analysis and visualized through multidimensional scaling (MDS). A total of 547 unique haplotypes were detected. The observed haplotype diversity and discrimination capacity were 0.9995 and 0.7745, respectively. The homogeneity of Sichuan Han population was detected when microareas were analyzed. This population exhibited no significant genetic difference to both of the minorities in reference databases, Mongolian and Manchu, which had been through mass ethnic amalgamation with Sichuan Han population in history.